Dévoiler le travail émotionnel : le consentement en question - Aurélia Dumas; Fabienne Martin-Juchat (Perspectives Interdisciplinaires sur le Travail et la Santé)
Given the methodological challenge of studying emotional work in professional situations, particularly in relation to the observability of affects, we must also include the need for an ethical reflection that nourishes the research practices themselves. In this article, we look more specifically at the question of the consent of workers participating in a study on the communication of emotions in a non-therapeutic work context. Emotional work is defined as an exercise in figuration, that is the presentation of self which operates in workers, either consciously or unconsciously. Analyzing this in a non-therapeutic context requires that the researcher observe the employees in a way that takes into account their interacting bodies, over and above what they say and intend to do. The problem here is twofold. It involves the concealment at the heart of emotional work, but also, in the professional sphere, the expectations of controlling and regulating emotions, which are largely internalized and incorporated by individuals at work. How can the social scientist capture these unspoken, unshown affects. And because they are hidden both from others and from oneself, what role can workers themselves play in understanding these hidden affects? We will discuss these issues by drawing on a number of partnership research projects (e.g., large companies, associations, hospitals).